Diverse Molecular Genotypes of Mycobacterium tuberculosis Complex Isolates Circulating in the Free State, South Africa - Anneke Van der Spoel van Dijk; Pakiso M. Makhoahle; Leen Rigouts; Kamaldeen Baba (International Journal of Microbiology)
Tuberculosis is a serious public health concern especially in Africa and Asia. Studies describing strain diversity are lacking in the Free State region of South Africa. The aim of the study was to describe the diversity of Mycobacterium tuberculosis (M. tuberculosis) strain families in the Free State province of South Africa. A total of 86 M. tuberculosis isolates were genotyped using spoligotyping. A 12-locus mycobacterial interspersed repetitive units-variable-number tandem repeats (MIRU-VNTRs) typing was used to further characterize the resulting spoligotyping clusters. SITVITWEB identified 49 different patterns with allocation to six lineages including Latin-American-Mediterranean (LAM) (18 isolates), T (14 isolates), Beijing (five isolates), S (six isolates), Haarlem (one isolate), and X (five isolates), while 37 (43.0%) orphans were identified. Eight clusters included 37 isolates with identical spoligotypes (2 to 13/cluster). MIRU-VNTR typing further differentiated three spoligotyping clusters: SIT1/Beijing/MIT17, SIT33/LAM3/MIT213, and confirmed one SIT34/S/MIT311. In addition, SpolDB3/RIM assignment of the orphan strains resulted in a further 10 LAM and 13 T families. In total, LAM (28 isolates) and T (27 isolates) cause 63% of the individual cases of MTB in our study. The Free State has a highly diverse TB population with LAM being predominant. Further studies with inclusion of multidrug-resistant strains with larger sample size are warranted.